2022
DOI: 10.1111/vru.13087
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging of dogs with perineal hernia reveals large prostates with morphological and spatial abnormalities

Abstract: The etiology of canine perineal hernia (PH) remains unclear, although as a disease of older male dogs, it is likely to be hormonal. The role of the prostate in the formation of PH has been questioned; however, prospective and systematic evaluation of prostates in these dogs is absent in the literature. In this prospective case–control study, CT imaging was used to assess prostatic changes in dogs with PH (n = 46) and compare these findings with those of intact age‐matched male dogs (n = 23). Using the OsiriX® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The hormone relaxin, mainly produced in the prostate in male dogs, is thought to leak into surrounding tissue from a cystic prostate in PH dogs [ 9 ]. This study did not assess the prostate, as CT findings of the prostate were recently published in a separate study, which found PH dogs to have significantly larger prostates than age-matched males, often with cysts [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hormone relaxin, mainly produced in the prostate in male dogs, is thought to leak into surrounding tissue from a cystic prostate in PH dogs [ 9 ]. This study did not assess the prostate, as CT findings of the prostate were recently published in a separate study, which found PH dogs to have significantly larger prostates than age-matched males, often with cysts [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This paper is part of a larger research project assessing the etiology and treatment of canine perineal hernia. The population of dogs in the present study also includes a cohort of male dogs from a previously published study [ 20 ]. We excluded dogs that had severe renal, hepatic, or cardiac disease or had an American Society of Anesthesiologists physical status rating of 4 or 5.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger project on PH in dogs. 8,15,16 Privately owned male dogs undergoing investigation of PH at the Veterinary Teaching Hospital of the University of Helsinki (VTHUH) were CT scanned before and 3 months after PH repair between 2017 and 2021. Power analysis was conducted to compare the clinical outcomes of two surgical techniques.…”
Section: Selection and Description Of Subjectsmentioning
confidence: 99%
“…The volume of the prostate was measured with a previously described and validated method. 8,16 Prostate margins were drawn manually on every sequential transverse image, and prostatic volume was then calculated using the software tool. To proportion the prostate volume to the size of the dog, the ratio between the cubic root of the volume to the length of the sixth lumbar vertebra was determined and recorded as ratio volume (RV).…”
Section: Evaluation Of the Prostatementioning
confidence: 99%
See 1 more Smart Citation